Comparison of the inhibitory effects of butterfly pea flower (Clitoria ternatea L.) extract and fermented milk probiotics on the growth of Salmonella sp. - Islamy, Aesthetica; Hermawati, Andyanita; Yuliastuti, Wiwid (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2025)
The increasing resistance of pathogenic bacteria such as Salmonella sp. to antibiotics has prompted the need for alternative antibacterial agents derived from natural sources. This study aimed to compare the inhibitory effects of prebiotics and probiotics against Salmonella sp. in vitro. The research was a laboratory experimental study using a post-test-only control group design. The prebiotic used was derived from butterfly pea flower (Clitoria ternatea L.) extract, while the probiotic was obtained from cow’s milk fermented with Lactobacillus casei. The test organism was Salmonella sp., obtained from a pure culture. The well diffusion method was used to evaluate antibacterial activity by measuring the diameter of the inhibition zone using a vernier caliper. Five concentrations (0.65%, 1.25%, 2.5%, 5%, and 10%) were tested in triplicate. The data were analyzed using descriptive statistics to calculate the mean inhibition zone diameter. At a concentration of 1.25%, the average inhibition zone of the probiotic was 8.08 mm, while the prebiotic produced a zone of 7.4 mm. Both agents showed larger inhibition zones compared to the negative control. The findings indicate that both prebiotics and probiotics exhibit antibacterial activity against Salmonella sp., with probiotics showing slightly stronger effects. These substances have the potential to be developed as natural antibacterial agents.